The Effect of The Implementation Of Tobacco Control Act 2007 On Financial Performance Of Cigarettes Manufacturing Firms In Kenya: The Case Of Bat Kenya Ltd - Mwaniki, Bernard Gathu (Machakos University, 2011)
Tobacco Control Act 2007 which became effective in Kenya from July 2008 was meant among others to regulate the production, sale, advertising and promotion of tobacco products and ultimately control cigarettes smoking. When the tobacco regulations were implemented by the government, the cigarettes manufacturing companies were up in arms complaining that the Act would put them out of business. This study sought to determine whether the Act has affected the financial performance of BAT (K) Ltd. Thus, the study sought to find out whether the Act has affected the trend of profit before tax, marketing expenditure, sale revenue of cigarettes, and staff benefits costs. Study involved collecting secondary data from BAT (K) Ltd’s Annual Financial Reports for the period 2006 to 2010. BAT was used as a case study as it controls 81% of the market share and company is therefore a good representative of the cigarettes manufacturers in Kenya. The study entailed a before-and-after implementation analysis and presentation of the financial data in form of time series graphs. The data analysis also involved use of tables, graphs and percentages that show trends that indicate the impact of the Act on the research variables. Descriptive research approach was used to interpret the data and draw conclusions. The study established that the Tobacco Control Act 2007 has affected the financial performance of BAT (K) Ltd as its annual profits before tax, marketing expenditure and staff-benefits costs have continued to reduce from 2009 after the Act was implemented. The study recommends that future Kenya government’s policies and regulation on sale and consumption of tobacco products should focus on educating tobacco consumers on health risks of smoking cigarettes (control demand) rather than imposing regulations on sale of cigarettes (control supply) which has had adverse effect on the financial performance of cigarettes manufacturing companies as revealed by this study.